Design & Development of Palm Oil Mill Maintenance Management System - Asmai, Siti Azirah; Hasan Basari, Abd Samad; Abdul Rahman, Ahmad Fadzli Nizam; Abal Abas, Zuraida (2006)
Maintenance management has always been a neglected area in management science and often considered as a secondary to production department. Maintenance engineers are expected to cope with maintenance problems without seeking to operate in a cost-effective or optimal manner. As a result, many companies are likely to experience massive maintenance expenditure and exceed its allocated budget. One of the approaches to solve the above matters is using a Computerized Maintenance Management System (CMMS). CMMS is a tool to help maintenance engineers manage their management system, which includes maintenance planning, scheduling, and purchasing, parts and inventory control. The needs of CMMS are still on demand to achieve the management objectives because it provides an information technology (IT) support. The project has chosen a palm oil mill as a case study to develop CMMS based on the user requirements. The features of this CMMS developed consist of Work Order, Preventive Maintenance, Inventory and Asset Management. Structured approach is used to develop this system by using Rapid Application Development (RAD) methodology. The completed system has been installed and implemented in United Bell Sdn Bhd. This research can be seen as initial step for further enhancement of maintenance technology incorporating with Information and Communication Technology (JCT).